Determination of Total Phenol and Flavonoid Contents and Antioxidant Activity from Extract Fraction of Sappan Wood (Caesalpinia sappan L.) by Liquid-Liquid Extraction and Vacuum Liquid Chromatography - Masturi; Alighiri, D.; Edie, S.S.; Hanisyifa, U.; Drastisianti, A. (Asian Journal of Chemistry, 2021)
This study reported the antioxidant activity of sappan wood (Caesalpinia sappan L.) extract and their extract fraction from the liquid-liquid extraction and vacuum liquid chromatography. The study comprises with phytochemical assessments, evaluation of total phenolic content (TPC) and total flavonoid content (TFC). The evaluation of antioxidant activity was carried out by using the DPPH method. The effectiveness of antioxidant activity in sappan wood compared to quercetin. Extract of sappan wood (ESW) yields of 5.40%, extract fraction from liquid-liquid extraction (FE LLE) yields of 52.15% and extract fraction from vacuum liquid chromatography (FE VLC) with silica gel and eluent sequential from n-hexane, 5% n-hexane/95% ethyl acetate, ethyl acetate and 5% ethyl acetate/45% methanol was produced 60 of fractions extract. The thin-layer chromatography (TLC) was analyzed using silica gel as a stationary phase with the mobile phase of n-hexane:ethyl acetate (1:0.55) was obtained 10 of fractions extract in fractions of 6 and 7, which showed the most positive results. The phytochemical test indicated the presence of phenolic and flavonoids compounds. The highest values for TPC was FE LLE (216.67 mg GAE/g), FE VLC 160.83 (mg GAE/g) and ESW (18.33 mg GAE/g), respectively. The highest values for TFC were F VLC (152.48 mg QE/g), FE LLE (66.2 mg QE/g) and ESW (48.4 mg QE/g), respectively. Then, the highest of antioxidants activity were F VLC (5.42 μg/mL), FE LLE (6.41 μg/mL), quercetin (6.52 μg/mL) and ESW (7.82 μg/mL), respectively. The results showed that the highest of TFC was related to the antioxidant activity. However, the highest value of TPC was not showed the highest antioxidant activity. Both ESW, FE LLE and FE VLC with quercetin as control exhibited powerful antioxidants.